The kinetics and mechanisms of the crystallisation of microporous materials - Francis, R; O'Hare, D (1998)
The synthesis of microporous materials is one of the major activities in contemporary solid state chemistry. This perspective brings together the current thinking regarding the synthesis and growth mechanisms of these technologically important materials. Also reviewed are the latest experiments being utilised to probe the complex chemistry which occurs during the synthesis of these materials.